IMPROVING ALGORITHM OF DETERMINING THE COORDINATES OF THE VERTICES OF THE POLYGON TO INVERT MAGNETIC ANOMALIES OF TWO-DIMENSIONAL BASEMENT STRUCTURES IN SPACE DOMAIN - Hang, Nguyen Thi Thu; Luan, Pham Thanh; Thanh, Do Duc; Minh, Le Huy (Vietnam Journal of Marine Science and Technology, 2018)
In this paper, we present an improved algorithm based on Murthy and Rao’s algorithm to invert magnetic anomalies of two-dimensional basement structures. Here, the magnetic basement interface is approximated by a 2N-sided polygon with assumption that the bottom of the basement is the Curie surface. The algorithm is built in Matlab environment. The model testing shows that the proposed method can perform computations with fast and stable convergence rate. The obtained result also coincide well with the actual model depth. The practical applicability of the method is also demonstrated by interpreting three magnetic profiles in the southeast part of the continental shelf of Vietnam.